Ocorrência de amblyomma longirostre em cyanocompsa brissonii no rio grande do sul, brasil - Gressler, Lucas Trevisan; Pereira, Larissa Quinto [UNESP]; Brustolin, Joice Magali; Lovato, Maristela; Monteiro, Sílvia Gonzalez (FapUNIFESP (SciELO), 2016)
Ticks are arthropods that are highly competent in transmitting pathogens to animals and humans. Among these, the genus Amblyomma is the most representative within the Neotropics. Amblyomma longirostre ticks are naturally distributed in countries of South, Central and North America. Their immature stages preferentially parasitize birds (Passeriformes), while adult stages are usually found on rodents. Therefore, reports of this tick species on wild hosts is epidemiologically relevant, especially because of these ticks’ potential for transmitting pathogens to other wild and domestic animals, and also to humans. Thus, the aim of this study was to report infestation by Amblyomma longirostre on Cyanocompsa brissonii in southern Brazil.
Occurrence of amblyomma longirostre in cyanocompsa brissonii in rio grande do sul, brazil
Keywords: Birds; Ixodidae; Parasitism; Ticks